2018
DOI: 10.1016/j.jchf.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and Incident Heart Failure and its Subtypes

Abstract: Objectives: To compare various measures of adiposity with risk for incident hospitalized heart failure (HF) with preserved ejection fraction (HFpEF) and reduced ejection fraction (HFrEF). Background: Obesity is a risk factor for HF, particularly HFpEF. It is unknown which measures of adiposity, including anthropometrics and computed tomography (CT)-measured fat area, are most predictive of HF sub-types. Methods: We studied 1,806 participants of the Multi-Ethnic Study of Atherosclerosis without baseline car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 32 publications
6
70
2
Order By: Relevance
“…The complex interaction between obesity and HF remains only partially understood. Obesity is a risk factor for HF but potentially more strongly so for HFpEF than for HFrEF 90 93 , whereas obesity has not been investigated specifically as a risk factor for HFrEF 86 . Secondary mitral regurgitation and right ventricular dysfunction have been reported to be less prevalent in HFmrEF and HFpEF than in HFrEF, whereas data on the epidemiology of secondary tricuspid regurgitation by EF phenotype are currently lacking 94 , 95 .…”
Section: Clinical Characteristics Of Hfmrefmentioning
confidence: 99%
“…The complex interaction between obesity and HF remains only partially understood. Obesity is a risk factor for HF but potentially more strongly so for HFpEF than for HFrEF 90 93 , whereas obesity has not been investigated specifically as a risk factor for HFrEF 86 . Secondary mitral regurgitation and right ventricular dysfunction have been reported to be less prevalent in HFmrEF and HFpEF than in HFrEF, whereas data on the epidemiology of secondary tricuspid regurgitation by EF phenotype are currently lacking 94 , 95 .…”
Section: Clinical Characteristics Of Hfmrefmentioning
confidence: 99%
“…Visceral adiposity was found to be associated with a higher risk of developing HF in the black population in the Jackson heart study [ 12 ]. The finding was supported with the outcome of MESA study, a large multiethnic U.S. study, which found that visceral adiposity was independently associated with the incidence of hospitalized patients with heart failure preserved ejection fraction (HFpEF) [ 13 ].…”
Section: Mechanism Of Metabolic Syndrome and Its Relation To Heart Famentioning
confidence: 74%
“…Consistently, studies have observed that risk of HF associated with VAT is driven by greater burden of cardiometabolic risk factors [ 5 , 33 ]. It is noteworthy that a more independent association between VAT and risk of HF has been reported, specifically with HF with preserved LVEF (HFpEF) [ 12 ]. Findings from our study suggest that the higher risk of HF, particularly HFpEF, in patients with higher amounts of VAT may be related to impairment in myocardial contractility independent of traditional CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…VAT has been associated with higher left ventricular (LV) mass and lower LV end diastolic volume (EDV) [ 5 , 9 ], while CRF has been associated with higher LV filling pressures and diastolic dysfunction [ 10 , 11 ]. These cardiac remodeling patterns may reflect intermediate phenotypes in the progression from at-risk to clinical HF [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%